Characteristics of Proteins from Fresh and Dried Residues of Soy Milk Production - Puechkamut, Yuporn; Panyathitipong, Woralak (Agriculture and Natural Resources, 2012)
Fresh soy milk residue (okara) received from a soy milk factory was dried at 60 °C to obtain dried okara. Proteins were extracted from fresh and dried okara at pH 9 and 80 °C. The results found that the greatest recovery of extracted protein from fresh okara was achieved with an extraction time of 2 h. The surface hydrophobicity of the protein extracted from dried okara was higher than that of fresh okara. The sodium dodecyl sulfate (SDS) patterns determined by polyacrylamide gel electrophoresis (PAGE) of okara protein isolates were similar to that of commercial soy protein. The okara protein isolates seemed to have better functionality in their emulsion stability, foam capacity and fat absorption capacity compared to commercial soy protein but not in water absorption capacity. There were no signiﬁ cant differences in the functional properties among proteins extracted from fresh and dried okara. The essential amino acid contents of okara protein isolate were comparable to those of the FAO scoring pattern with the exception of valine, tyrosine and sulfur-containing amino acids.